2018
DOI: 10.1111/ijpp.12460
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice of final-year student pharmacists in public health in Namibia, Zambia and Zimbabwe: an exploratory survey

Abstract: Final-year student pharmacists in Namibia, Zambia and Zimbabwe express strong interest in public health education and involvement in public health activities. This interest and enthusiasm can serve as evidence for advancing public health education in the pharmacy curricula and for developing pharmacist opportunities in public health efforts that match the needs of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Competencies in upholding professionalism were described (Pfleger et al, 2008;Walsh et al, 2012;Bzowyckyj & Janke, 2013;Bryson et al, 2014;; J. R. Covvey & Ryan, 2018;Law et al, 2019). The display of professional and ethical behaviour, leadership, respect and understanding for others were described as important foundational attributes for pharmacists in public health roles (Walsh et al, 2012;Bzowyckyj & Janke, 2013;Bryson et al, 2014;Benzian et al, 2015;; J. R. Covvey & Ryan, 2018;Johnson & Traynor, 2018;).…”
Section: Roles and Professional Qualitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Competencies in upholding professionalism were described (Pfleger et al, 2008;Walsh et al, 2012;Bzowyckyj & Janke, 2013;Bryson et al, 2014;; J. R. Covvey & Ryan, 2018;Law et al, 2019). The display of professional and ethical behaviour, leadership, respect and understanding for others were described as important foundational attributes for pharmacists in public health roles (Walsh et al, 2012;Bzowyckyj & Janke, 2013;Bryson et al, 2014;Benzian et al, 2015;; J. R. Covvey & Ryan, 2018;Johnson & Traynor, 2018;).…”
Section: Roles and Professional Qualitiesmentioning
confidence: 99%
“…It was identified that pharmacists are responsible for contributing to the community and its health and wellbeing (Jarvis et al, 2004;Pfleger et al, 2008;DiVall et al, 2013;Bryson et al, 2014;Jogerst et al, 2015;Interprofessional Education Collaborative, 2016;Scott et al, 2016;J. R. Covvey & Ryan, 2018;Johnson & Traynor, 2018;Law et al, 2019). The identification of factors that have impact on people's health and pharmacists contribution to community health assessments were described as important to inform appropriate pharmacy interventions (Boyle et al, 2004;Scott et al, 2016;Holden & Evans, 2019;Law et al, 2019).…”
Section: Warren Et Almentioning
confidence: 99%
See 3 more Smart Citations